Is anterior temporal lobectomy a precipitating factor for transient global amnesia?. Issue 3 (21st November 2007) - Dupont, S; Samson, S; Baulac, M
Abstract : Little is known about the pathophysiology of transient global amnesia (TGA) and how it is related to epilepsy. We report here five typical episodes of TGA, each occurring several years after surgery for epilepsy. In all cases, patients were seizure-free after a surgery consisting of anterior temporal lobectomy for refractory medial temporal lobe epilepsy associated with hippocampal sclerosis (n = 4) or linked with a dysembryoplastic neuroepithelial tumour (n = 1). Investigations, including MRI or CT scan, angio-MRI or echocardiogram or vascular echo Doppler, excluded a vascular origin. Using accepted criteria to distinguish between TGA and epileptic amnesic attacks—the typical clinical presentation, the long duration of the episode, the absence of other symptoms associated with seizures and the absence of recurrence—it is evident that these patients suffered a TGA. These studies suggest that hippocampal resection carried out therapeutically in some epileptic patients may be a precipitating factor for TGA.